2015
DOI: 10.1016/j.gde.2015.08.004
|View full text |Cite
|
Sign up to set email alerts
|

Applications of comparative evolution to human disease genetics

Abstract: Direct comparison of human diseases with model phenotypes allows exploration of key areas of human biology which are often inaccessible for practical or ethical reasons. We review recent developments in comparative evolutionary approaches for finding models for genetic disease, including high-throughput generation of gene/phenotype relationship data, the linking of orthologous genes and phenotypes across species, and statistical methods for linking human diseases to model phenotypes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 91 publications
0
4
0
Order By: Relevance
“…The meeting also featured several algorithmic contributions. Of particular note was work presented by Benjamin Liebeskind and Claire McWhite (University of Texas at Austin, USA) that leveraged conserved protein networks to better discern between paralogs and orthologs, focusing on networks that are involved in or associated with human diseases ( Liebeskind, 2016 ; McWhite et al , 2015 ). Similarly Klaas Vandepoele (University of Ghent – VIB, Belgium) compares gene expression level commonalities across different plant species to gain additional insight for correctly identifying functionally conserved (co-) orthologs showing conserved spatial-temporal expression ( Movahedi et al , 2012 ; Tzfadia et al , 2016 ).…”
Section: Algorithmic Advancesmentioning
confidence: 99%
“…The meeting also featured several algorithmic contributions. Of particular note was work presented by Benjamin Liebeskind and Claire McWhite (University of Texas at Austin, USA) that leveraged conserved protein networks to better discern between paralogs and orthologs, focusing on networks that are involved in or associated with human diseases ( Liebeskind, 2016 ; McWhite et al , 2015 ). Similarly Klaas Vandepoele (University of Ghent – VIB, Belgium) compares gene expression level commonalities across different plant species to gain additional insight for correctly identifying functionally conserved (co-) orthologs showing conserved spatial-temporal expression ( Movahedi et al , 2012 ; Tzfadia et al , 2016 ).…”
Section: Algorithmic Advancesmentioning
confidence: 99%
“…Applying a simple hypothesis to a multifactorial problem delays progress in understanding the etiology and development of applicable tests; for example, this type of approach significantly delayed understanding the etiology of atherosclerosis. 10 The Comparative Approach McWhite et al 24 provide a recent review on the comparative approach and its application to human disease research, including advances in technique that can be used to elucidate and understand PQ neurotoxicity. The multifactorial approach is complementary to the comparative approach.…”
Section: Part I: Laboratory Context Animal Modelsmentioning
confidence: 99%
“… McGary et al (2010) found many such associations, discovering equivalent gene modules involved in human diseases and mutant phenotypes in model organisms ( ). Additionally, better predictions should emerge as more GI data from model organisms, particularly higher eukaryotes, are obtained ( Golden, 2017 ; McWhite et al, 2015 ; Woods et al, 2013 ).…”
Section: Using Model Organisms To Discover Gene–phenotype Association...mentioning
confidence: 99%